Music and psychoacoustic perception abilities in cochlear implant users with auditory neuropathy spectrum disorder - ÇİPRUT, AYŞE AYÇA; YÜKSEL, MUSTAFA (ELSEVIER IRELAND LTD, 2020)
Objective: Auditory neuropathy spectrum disorder (ANSD) is a condition wherein the pre-neural or cochlear outer hair cell activity is intact, but the neural activity in the auditory nerve is disrupted. Cochlear implant (CI) can be beneficial for subjects with ANSD; however, lithe is known about the music perception and psychoacoustic abilities of CI users with ANSD. Music perception in CI users is a multidimensional and complex ability requiring the contribution of both auditory and nonauditory abilities. Even though auditory abilities lay the foundation, the contribution of patient-related variables such as ANSD may affect the music perception. This study aimed to evaluate the psychoacoustic and music perception abilities of CI recipients with ANSD. Study design: Twelve CI users with ANSD and twelve age- and gendermatched CI users with sensorineural hearing loss (SNHL) were evaluated. Music perception abilities were measured using the Turkish version of the Clinical Assessment of Music Perception (T-CAMP) test. Psychoacoustic abilities were measured using the spectral ripple discrimination (SRD) and temporal modulation transfer function (TMTF) tests. In addition, the age of diagnosis and implantation was recorded. Results: Pitch direction discrimination (PDD), timbre recognition, SRD, and TMTF performance of CI users with ANSD were concordant with those reported in previous studies, and differences between ANSD and SNHL groups were not statistically significant. However, the ANSD group performed poorly compared with SNHL group in melody recognition subtest of T-CAMP, and the difference was statistically significant. Conclusion: CI can prove beneficial for patients with ANSD with respect to their music and psychoacoustic abilities, similar to patients with SNHL, except for melody recognition. Recognition of melodies requires both auditory and non-auditory abilities, and ANSD may have an extensive but subtle effect in the life of CI users.
Keywords: Cochlear implant; Auditory neuropathy spectrum disorder; Music perception; Psychoacoustic; TEMPORAL-MODULATION DETECTION; NORMAL-HEARING; SPEECH-PERCEPTION; GAP-DETECTION; RIPPLE DISCRIMINATION; CLINICAL-ASSESSMENT; CHILDREN; ADULTS; AGE; NEUROPLASTICITY